« Barrer la voie au syndicalisme »: les manœuvres de l’État québécois contre la Société bienveillante des journaliers de navires de Québec et les autres sociétés de secours mutuel, 1869–1899 - Bischoff, Peter (Labour / Le Travail)

(untitled) (Canadian Committee on Labour History, 2009)
Abstract An important wood export centre, Quebec’s port was also an extraordinary place for experimenting with mutualism and trade unionism. The dockers, Irish and French Canadian, paved the way by organizing and incorporating a mutual assistance company in 1862 under an Act of the Parliament of Lower Canada. In 1865, they demanded a salary standard. Two years later, ten union clauses were added to the rules of their association. Combining mutualism and trade unionism, they built rapidly the most powerful local union organization in the country. This transformation of a ‘mutual assistance company into a trade union’ gave rise to imitators among boatmen, stevedores, etc. It also raised fear among commercial, judicial and political elites. What followed was a battle on several fronts aimed at bringing back the company of dockers to functions purely mutualist, and by the mere fact of closing the door on an organizing method judged socially dangerous for the established order. Despite the fact that the workers did not disarm, the Quebec government succeeded in reducing substantially the ‘zone of tolerance’ of mutualism in its territory.